Redescobrindo Antonieta Dias de Moraes: contribuições do estudo interdisciplinar de sua correspondência passiva (1950 A 1975) - Menezes, Ivanildes Regina de (Universidade Federal de São Carlos, 2022)
Antonieta Dias de Moraes name is not very well remember in the historiography of the Brazilian juvenile literature. She, as a writer and translator, received the titles of “communist poetess” and “Brazilian ambassador of the juvenile literature abroad” from the Brazilian national media in different times. She published more than 50 books among her own copyright work and translations – such as translations of the Guatemalan Miguel Asturias, Nobel Prize in Literature in 1967 – as well as acted and contributed in the debates concerning culture and publishing market, awarded and regarded as a juvenile publishing market success abroad. The “deafening silence” concerning her works raise questions regarding the reasons that derailed her name in the Brazilian national literature scene. The present research aims to add on the efforts undertaken by Antonieta Dias de Moraes Fund (Fundo ADM) since 2011, whose archives are under the care of the Federal University of São Carlos (UFSCar), the Santa Eudóxia Farm and the author’s heirs. By promoting the dialogue between Literature, Language Studies and Science, Technology and Society Studies (STS) reflections that arise from the author’s passive correspondence collection’s utterances are proposed, collection which comprises 17 unreleased letters comprehending Antonieta’s biggest production period (1950 till 1975) and are written in the core of the political transitions which immersed the country in the foul authoritarianism of the Military Dictatorship. The option for an interdisciplinary approach applied to STS aims to highlight the relation between the social and ideological factors bringing forth the meanings hidden in between the lines of the ideological constructed sayings in the corpus of the research. Therefore before us lay fragments of this notable writer comprised in the voices and visions of her friends such as Zélia Gattai, Jorge Amado, Vasconcelos Maia and Cecilia Meireles, her correspondents. The theme’s complexity required the review of the literature related to two discourse theories in which the processes and views of the research object are based: the French Discourse Analysis proposed by Michel Pêcheux and the heteroglossia theory by Mikhail Bakhtin as well as Brazilian literary studies in different hues. The present thesis aim to demonstrate that the discourses of the correspondents in the analysed letters accommodate the subject of Antonieta as a product of the live interaction of social forces. Through this process, the strict interdisciplinary relation with the language studies in the investigation of the development processes and STS focused pratices is highlighted. The knowledge about different fields, articulated between themselves, contributed to achieved result following a dynamic mural of Antonieta Dias de Moraes’ intellectual production, fulfilling the triple function of valorizing the protection of writers’ personal archives, systematizing information in a critical manner and spreading academical knowledge in accessible language. Despite the lack of attention for the author’s literary texts in this moment, we can assert that the passive correspondence collection creates a narrative for Antonieta and prompts us in the passionate mission of fulfilling the gaps in recreating her artistic life. We can also suggest that new studies are attained to continuously describe the documents contained in the ADM fund in order to review, update and prototype tools that add to the elaboration of public policies in science, technology and innovation between Sciences, simultaneous to the woman-written Brazilian literature memory rescue. Equally important is the study of Antonieta Dias de Moraes’ vast literary opus, more than ever diverse in gender and inspiring in her themes and values defending the Peace between the People.
Redescovering Antonieta Dias de Moraes: the contribution of her passive correspondence’s interdisciplinary study (1950 to 1975)
Keywords: Fundo Antonieta Dias de Moraes; Correspondência passiva; Interdisciplinaridade; Ciência, tecnologia e sociedade; Análise do discurso; Antonieta Dias de Moraes Fund; Passive correspondence; Interdisciplinarity; Science, technology and society; Discourse analysis; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUA PORTUGUESA